FACTORS ASSOCIATED TO ADHERENCE TO DIFFERENT TREATMENT SCHEMES WITH MEGLUMINE ANTIMONIATE IN A CLINICAL TRIAL FOR CUTANEOUS LEISHMANIASIS - Madelon Novato Ribeiro; Maria Inês Fernandes Pimentel; Armando de Oliveira Schubach; Raquel de Vasconcellos Carvalhães de Oliveira; José Liporage Teixeira; Madson Pedro da Silva Leite; Monique Fonseca; Ginelza Peres Lima dos Santos; Mariza Matos Salgueiro; Erica de Camargo Ferreira e Vasconcellos; Marcelo Rosandiski Lyra; Mauricio Naoto Saheki; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The favorable outcome of the treatment of a disease is influenced by the adherence to therapy. Our objective was to assess factors associated with adherence to treatment of patients included in a clinical trial of equivalence between the standard and alternative treatment schemes with meglumine antimoniate (MA) in the treatment of cutaneous leishmaniasis (CL), in the state of Rio de Janeiro. Between 2008 and 2011, 57 patients with CL were interviewed using a questionnaire to collect socioeconomic data. The following methods were used for adherence monitoring: counting of vial surplus, monitoring card, Morisky test and modified Morisky test (without the question regarding the schedule); we observed 82.1% (vial return), 86.0% (monitoring card), 66.7% (Morisky test) and 86.0% (modified Morisky test) adherence. There was a strong correlation between the method of vial counting and the monitoring card and modified Morisky test. A significant association was observed between greater adherence to treatment and low dose of MA, as well as with a lower number of people sleeping in the same room. We recommend the use of the modified Morisky test to assess adherence to treatment of CL with MA, because it is a simple method and with a good performance, when compared to other methods.